2012
DOI: 10.1111/j.1467-8543.2010.00787.x
|View full text |Cite
|
Sign up to set email alerts
|

Teamwork, Skill Development and Employee Welfare

Abstract: There has been a sharp divergence in the literature about the benefits of teamwork. Some have claimed that it is solely in the interests of management, others that it is beneficial for employees and yet others that it makes little difference to either productivity or well-being. This article draws upon the British Skills Survey Series. It shows that while teamwork did expand between the early 1990s and 2006, this was due primarily to the growth of the type of teamwork that allowed employees little in the way o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
98
0
9

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 88 publications
(113 citation statements)
references
References 48 publications
6
98
0
9
Order By: Relevance
“…Finally, in this study, it was found that teamwork has a positive impact on the employees' organisational commitment. This is consistent with the findings in the work of Gallie, Zhou, Felstead andGreen (2009), Okoo (2013), Zincirkiran, Emhan and Yasar (2015).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Finally, in this study, it was found that teamwork has a positive impact on the employees' organisational commitment. This is consistent with the findings in the work of Gallie, Zhou, Felstead andGreen (2009), Okoo (2013), Zincirkiran, Emhan and Yasar (2015).…”
Section: Resultssupporting
confidence: 82%
“…Hanaysha (2016) asserted that teamwork not only promotes employees' organisational commitment but also increases their productivity; it is also a platform for knowledge sharing among team members. In the same vein, Gallie, Zhou, Felstead and Green (2009) found that teamwork promotes employees' organisational commitment and increases their productivity. Zincirkiran, Emhan and Yasar (2015) found a positive influence of teamwork on organisational commitment among the health workers in Turkey.…”
Section: Teamworkmentioning
confidence: 92%
“…Cottini and Lucifora 2013). There is also evidence that well-being is enhanced where the teams through which work is organised are granted some influence over tasks, choice of team members and team leader Gallie et al 2012). According to the 'demand-control' model, the impact of task discretion on well-being is greater where work intensity is high, because higher task discretion allows workers to partially counter the stressful effects of high-intensity work (Karasek 1979;Karasek and Theorell 1990).…”
Section: Participationmentioning
confidence: 99%
“…Most studies using job requirements indicators have focused on the hedonic pay premium associated task discretion of the individual was being increasingly substituted by and subordinated by the influence of the team on tasks. Gallie et al (2010) found that this was not the case. Looking at the period up till 2006, teamworking had indeed become more prevalent, but the decline of individual discretion was not at all counterbalanced by a rise in the proportion working in teams where there was a high level of team influence on tasks (defined as "self-directing teams").…”
Section: The Value Of Influence Skills and Computing Skillsmentioning
confidence: 75%
“…Team working, it is hypothesised, enhances learning through multi-functional working, and through a collaborative context that provides feedback and advice between team members. Gallie et al (2010) verify this hypothesis, but show that it is only valid for self-directing teams. Those who work in non-self-directing teams have no advantage over those who do not work in teams at all.…”
Section: Skill Increases and Changes In Work Organisationmentioning
confidence: 76%